3D Modeling and Printing in Physics Education: The Importance of STEM Technology for Interpreting Physics Concepts - Indira Usembayeva; Bakitzhan Kurbanbekov; Sherzod Ramankulov; Aknur Batyrbekova; Kazhymukan Kelesbayev; Asem Akhanova (Qubahan Academic Journal)
In accordance with the requirements of STEM education, a physics teacher must know the principle of operation, the device of the equipment and be able to effectively apply it in physics lessons. If, during a physics experiment, students do not know the principle of operation of the installation, then they also remain unclear how the physics phenomenon occurs in the experiment. If the experimental textbooks in the physics classroom are old, unusable, or there are no physics overloads, it is necessary that the teacher can consider a way to solve this problem and quickly make a decision using modern technologies (for example, 3D printing) to eliminate or alleviate the problem. The aim of this study is to address the challenges faced by physics educators in using outdated or unavailable laboratory equipment. The purpose of this study is to determine the importance of 3D modeling and printing based on STEM technology for performing physics laboratory work. In addition, it is necessary to determine the features of the use of 3D modeling and printing in the interpretation of physics concepts. This study employs a descriptive correlational approach, utilizing both a meta-analysis of relevant literature and a student questionnaire. In the course of the study, a meta-analysis of scientific papers based on the PRISMA method was conducted and a student questionnaire method was obtained. Based on 3D computer programs, a modeling method and constructive printing methods were chosen. These results underscore the need for integrating modern technologies into physics education to foster a deeper understanding and engagement with scientific phenomena. The results of the responses of 64 surveyed students significantly expand the teaching experience - using 3D modeling and printing technologies compared with traditional forms of education. The results of the study are recommended for use in the field of STEM education and are a necessary document for a large audience of researchers in the future.